(untitled) (Perner’s Contacts, 2014)
Paper deals with the allocation of modern logistics centers and intermodal terminals in the context of improving the quality of transport and logistics services. The optimal allocation of public logistics centers allows the creation of a network of public logistics centers in the territory with an emphasis on non-discriminatory access and the public interest.